2021
DOI: 10.3390/ijms22169095
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Inactivation of Legionella pneumophila Biofilm Formation by Cationic Tetra- and Tripyridylporphyrins in Waters of Different Hardness

Abstract: The bacterium Legionella pneumophila is still one of the probable causes of waterborne diseases, causing serious respiratory illnesses. In the aquatic systems, L. pneumophila exists inside free-living amoebae or can form biofilms. Currently developed disinfection methods are not sufficient for complete eradication of L. pneumophila biofilms in water systems of interest. Photodynamic inactivation (PDI) is a method that results in an antimicrobial effect by using a combination of light and a photosensitizer (PS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Antiviral PDTs have been applied in numerous clinical studies of recurrent HSV-1 infections, and, although this has been largely successful and promising, standardized protocols have yet to be established [ 25 , 40 , 41 ]. In this study, we investigated the potential of water-soluble TMPyP3-C17H35, a porphyrin-based tricationic PS that has shown excellent 1 O 2 production and PDT efficacy in suppressing L. pneumophila in our previous study [ 28 , 29 ], to inhibit HSV-1 replication. We observed relatively rapid internalization (<30 min) of TMPyP3-C17H35 into Vero cells and its accumulation into structures that resemble lysosomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antiviral PDTs have been applied in numerous clinical studies of recurrent HSV-1 infections, and, although this has been largely successful and promising, standardized protocols have yet to be established [ 25 , 40 , 41 ]. In this study, we investigated the potential of water-soluble TMPyP3-C17H35, a porphyrin-based tricationic PS that has shown excellent 1 O 2 production and PDT efficacy in suppressing L. pneumophila in our previous study [ 28 , 29 ], to inhibit HSV-1 replication. We observed relatively rapid internalization (<30 min) of TMPyP3-C17H35 into Vero cells and its accumulation into structures that resemble lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the benefits of photodynamic therapy have already been demonstrated for the treatment of herpes labialis [ 25 ] and herpetic keratitis [ 26 ]. We have recently shown that TMPyP3-C 17 H 35 ( Figure 1 ), a tricationic porphyrin-based PS with a long alkyl chain, synthesized in our laboratory [ 27 ], effectively inhibits Legionella pneumophila , an environmental bacterium and an opportunistic pathogen that causes Legionnaires’ disease [ 28 , 29 ]. Compared to other tested PSs, the compound showed superior properties in blocking L. pneumophila replication and biofilm formation, indicating a potential application in disinfection [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the same PSs were tested against L. pneumophila serogroup 1, strain Philadelphia ST1, in three samples of water with different hardness taken from water wells. An amphiphilic porphyrin with a long alkyl chain, TMPyP3-C 17 H 35 , was shown to be the most affected by ions present in water samples (such as Cl − , Mg 2+ , Ca 2+ ) and prone to aggregation, and although it showed a very high 1 O 2 production, which was significantly higher than for the other two PSs, and efficient PDI, it was very unstable in water samples with higher concentrations of ions, especially with repeated irradiations [145]. In contrast, two hydrophilic porphyrins (TMPyP3 and TMPyP3-CH 3 ) were stable in all water samples over five days, whether irradiation was carried out only on the first day, or repeated every 24 h, so it was concluded that they could be more useful in the applications with repeated irradiations and where PDI is needed against Legionella over longer time periods, while TMPyP3-C 17 H 35 where high activity is rapidly required [145].…”
Section: Legionella Pneumophilamentioning
confidence: 99%
“…In the last few years, our group has studied PDI with exogenous PSs on L. pneumophila, comparing the activity of three water soluble cationic porphyrins, two of which were hydrophilic, tetracationic 5,10,15,20-tetra(N-methylpyridinium-3-yl)porphyrin tetrachloride (TMPyP3) and tricationic 5-(4-acetamidophenyl)-10, 15,20-tri(N-methylpyridinium-3-yl)porphyrin trichloride (TMPyP3-CH 3 ), and one which was significantly more lipophilic due to a long alkyl chain, tricationic 5-(4octadecanamidophenyl)-10,15,20-tris(N-methylpyridinium-3-yl)porphyrin trichloride (TMPyP3-C 17 H 35 ) [143][144][145]. Lipophilic TMPyP3-C 17 H 35 binds to L. pneumophila (serogroup 1, strain 130b) cell already after 10 min [143], but also tight binding to the bacterial cell within 10 min was shown with hydrophilic porphyrins TMPyP3-CH 3 and TMPyP3 [144], and very low minimum effective concentrations (MEC) values (from 0.024 µM to 0.39 µM) were obtained for all three PSs after irradiation for 10 min with violet light (394 nm, 20 mW/cm 2 ) [144].…”
Section: Legionella Pneumophilamentioning
confidence: 99%